Determinants of private investment in developing countries - Mulu, Gebreeysus (KDI School, 1998)
Korea and Taiwan are known for their impressive economic performance and ability to join the industrial economies within short period of time. The rapid and persistent accumulation of physical capital in both countries is considered to be one of the special phenomenon and that account the large portion of economic accomplishment Hence, the paper examines the factors behind the rapid capital accumulation under the heading of determinants of private investment in Korea and Taiwan. The study seeks to assess the possible impact of different factors for the unwavering investment growth in these countries in light of developing countries. As a means of methodology and addressing the controversy about government intervention, the study contrasts the likely effect of quantity and relative price variables in determining private investment decision in these countries. In this regard, availability of fund, accessibility of foreign exchange, government investment and existence of sufficient skilled manpower and capital cost are explored The thorough assessment of the rapid investment growth in these countries reveals the complex channel through which government policies affected private investment. Investors in both countries depend largely on borrowing while the contribution of capital market was almost negligible. Government heavily intervened in the financial market tO foster investment through different instruments such as, interest rate control, rationing of available credit to preferred sectors and mobilizing of savings as well. The contribution of government investment in total fixed investment was large, particularly in Taiwan about half. In both countries the incentive structure for investors was so diversified. Tax structure was generous and selective. Governments also encouraged private investors by sharing risk, facilitating market domestic and abroad. The study provides empirical evidence on the determinants of private investment. The model specifies three main components; demand, resource (quantity) availability and cost of capital as determinants. The common problem of spurious correlation in investment functions is addressed by testing the time series for stationarity and insuring that residuals from the econometric estimation are white noise. Two step estimation; regression at levels and dynamic model of the diffemced variables is employed. The use of these two different estimation techniques helped to confirm the validity of the model From the empirical test, it is found that the private investment has been largely affected by demand factors (domestic as well as foreign). Fund availability was also crucial factor, suggesting the importance of this variable in resource constrained and interest rate administered countries. Public investments have been found to compliment rather than crowding out the private investment in both countries. Private investment was quite sensitive to relative price of capital goods and output. While effect of interest rate was not that much significant. The results affirm the positive role of government in boosting private investment in both countries. The positive effect of quantity of credit and public investment obtained undoubtedly takes explicit account of government contribution. Indeed, the other variables were not free of government hands. Both governments boosted demand for domestic production through policies that prosper the domestic economy and their special export promotion strategy. They maintained lower relative price of capital goods through tax, tariff and other mechanisms such as, domestic market protection.
Thesis(Master) --KDI School:Master of Growth and Development Studies,1998